Optimizing synthesis parameters to compare Ag2V4O11/AgVO3 nanosheets for electrochemical energy storage - Poria Gomrokchi; Maryam Ghiyasiyan-Arani; Mehdi Shabani-Nooshabadi; Masoud Salavati-Niasari (Alexandria Engineering Journal)
This work investigates the effects of altering silver vanadate structures as active materials in energy storage. Enhancing the low conductivity of vanadium oxide-based compounds can be achieved by low dimensional morphology. The synthesis of electrode materials was carried out using a hydrothermal approach in the presence of TrenSal ligand to tailor the shape of two-dimensional nanosheets. The TrenSal ligand prepared by tris(2-aminoethyl) amine and salicylaldehyde. Also, effect of pH on the purity of samples was investigated which confirmed by XRD diffractograms. The microstrain of synthesized samples calculated using Williamson-Hall plots to study the effect of synthesis condition of the structure tension. The nanosheets of silver vanadate by thickness of 30 nm which synthesized in the presence of 1.5 mol of ligand show the highest capacity at 15th cycle about of 314 mAhg−1. Hence, employing a two-dimensional (2D) structure for the can be suitable for hydrogen storage in the electrodes made of silver vanadate (AGV). The AGV electrodes can save the hydrogen by redox and physisorption mechanisms.